2020
DOI: 10.1186/s13287-020-01832-2
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular vesicles from human mesenchymal stem cells expedite chondrogenesis in 3D human degenerative disc cell cultures

Abstract: Background Extracellular vesicles (EVs) from human mesenchymal stem cells (hMSCs) are known to be mediators of intercellular communication and have been suggested as possible therapeutic agents in many diseases. Their potential use in intervertebral disc (IVD) degeneration associated with low back pain (LBP) is yet to be explored. Since LBP affects more than 85% of the western population resulting in high socioeconomic consequences, there is a demand for exploring new and possibly mini-invasive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
1
26
0
1
Order By: Relevance
“…The up-modulation of TIMP-1 and downmodulation of MMP-1/MMP-3 also indicate a healthier balance between catabolism and anabolism. Similar findings were presented by Hingert et al (2020) When comparing degenerated disc cell pellets treated with MSC-derived exosomes to control cultures, it was observed that ECM synthesis was over three times greater in the treated pellets. MMP-1 secretion in the degenerated disc cells was similarly reduced as a result of the exosome therapy.…”
Section: Impacts Of Msc-derived Exosomes On Ivddsupporting
confidence: 84%
See 1 more Smart Citation
“…The up-modulation of TIMP-1 and downmodulation of MMP-1/MMP-3 also indicate a healthier balance between catabolism and anabolism. Similar findings were presented by Hingert et al (2020) When comparing degenerated disc cell pellets treated with MSC-derived exosomes to control cultures, it was observed that ECM synthesis was over three times greater in the treated pellets. MMP-1 secretion in the degenerated disc cells was similarly reduced as a result of the exosome therapy.…”
Section: Impacts Of Msc-derived Exosomes On Ivddsupporting
confidence: 84%
“…For these biochemical challenges, exosomes produced from MSCs have been shown to have a protective impact on NPCs via the mechanism of increasing the expression of chondrocytes, aggrecan, and collagen II in the extracellular matrix and decreasing matrix disintegration via the mechanism of the down-modulation of matrix-degrading enzymes. Moreover, the effects of MSC-derived exosomes on ECM metabolism in IVD cells without any biochemical challenge have also been investigated ( Lu et al, 2017 ; Hingert et al, 2020 ). One study ( Lu et al, 2017 ) showed that after the intervention of exosomes derived from MSC, the ECM expression in degenerated nucleus pulposus cells increases significantly.…”
Section: Impacts Of Msc-derived Exosomes On Ivddmentioning
confidence: 99%
“…Exosomes inhibited H 2 O 2 -induced NLRP3 inflammasome activation, drastically reduced the catabolic action of MMP-3, MMP-13, IL-6 and inducible nitric oxide synthase (iNOS), repressed reactive oxygen species (ROS) generation and mitochondrial dysfunction was restored [113]. Hingert et al have reported the potential abilities of MSC-derived EVs in a 3D in vitro model to improve cell viability, proliferation, ECM production, apoptosis, chondrogenesis and cytokine secretion in NPCs harvested from patients with IDD and chronic LBP [114]. Furthermore, an actual challenge is the potential of engineered EVs to lead NPC towards a healthy NP-like phenotype, decrease catabolism and inflammation, and improve GAG accumulation both in vitro and in vivo.…”
Section: Authors Type Of Study Potential Role Of Evs Resultsmentioning
confidence: 99%
“…The knockdown of RASSF5 is suspected to decrease apoptotic cells. An in vitro study on the efficacy of hBMSC-derived exosomes resulted in more than a 50% increase in cell proliferation and decreases in cellular apoptosis in 3D human degenerative disc cell cultures, and ECM production was observed as early as day 7 [ 125 ]. NP cell-derived exosomes can not only induce the differentiation of MSCs into NP-like cells in vitro, but were also found to promote the migration of MSCs and the downregulation of the Notch1 pathway [ 126 , 127 ].…”
Section: Stem Cell-derived Exosomes As a Treatment For Ivddmentioning
confidence: 99%